Potential Use of Ambient-Cured Geopolymers for Intermediate Level Nuclear Waste Storage. (16th March 2018) - Ukritnukun, Supphatuch; Sorrell, Charles Christopher; Gregg, Daniel; Vance, Eric R.; Koshy, Pramod
Abstract: There is growing interest in reducing the use of ordinary Portland cement (OPC) owing to its high energy consumption and CO2 emissions. An environmentally-friendly alternative is the use of geopolymers, which can potentially reduce direct CO2 emissions through the appropriate choice of raw materials, mix design, and curing regimes. In this regard geopolymer mortars are also realistic candidates for the replacement of OPC mortars in nuclear waste immobilisation applications as they provide a more durable incorporation matrix as well as suppressing the formation of radiolytic hydrogen. The advantages of geopolymers over OPC for nuclear waste immobilisation include i) lower water content as alkaline activator is the main component that drives geopolymerisation, ii) higher thermal stability (<600°-800°C) compared to OPC concrete (<300°C), iii) higher compressive strength (50-80 MPa), and iv) lower leachability of radioactive ions when the mix design and curing temperature are appropriately balanced. UNSW and ANSTO have embarked on a long-term research program to investigate the possibility of using geopolymers for the immobilisation of Intermediate Level Liquid Waste (ILLW), the focus of which will be around the influence of gamma-irradiation on the durability.